Intervenciones de enfermería en el control del dolor del paciente postquirúrgico: revisión sistemática - Villegas Vega, María Ximena (2025)
Introduction: Pain control in post-surgical patients is fundamental for an optimal recovery, since proper pain management not only improves the well-being and quality of life of a patient. Objective: To describe the nursing interventions for pain prevention in post-surgical patients through a systematic review. Methodology: Qualitative approach was applied by analyzing and synthesizing the findings of previous studies on nursing intervention in post-surgical pain management by using the PRISMA methodology to structure the literature review which included a thorough search, a rigorous selection, a detailed data extraction, a critical evaluation of quality, and an analytical synthesis ensuring transparency and rigor in reporting findings. Results: The most effective strategies of pain management combine pharmacological and non-pharmacological interventions which are applied according to their specific needs of each patient; for this reason, the nursing interventions including the administration of analgesics, the use of relaxation techniques, early mobilization, emotional support, and preoperative education have been shown to significantly reduce post-surgical pain intensity, to improve the patient’s experience and to facilitate a faster and less complicated recovery. Conclusion: Nursing interventions that integrate non-pharmacological techniques such as the acupuncture, therapeutic massages, and transcutaneous electrical nerve stimulation have proven to be valuable complements to traditional strategies to manage pain since these techniques do not only contribute to reducing analgesic medications.